2015
DOI: 10.1007/s10735-015-9634-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the presence of clofazimine and its distribution in the healthy mouse brain

Abstract: This is the first report of clofazimine (CFZ) penetration and distribution in normal mouse brain. Mice were administered 25 mg/kg CFZ or 100 mg/kg CFZ orally, daily for 2 weeks. Animals were sacrificed and blood and brain tissues were harvested. Liquid chromatography tandem mass spectrometry showed high concentrations of CFZ in homogenized brain, with 100 mg/kg dose having significantly higher concentration than 25 mg/kg. Matrix-assisted laser desorption/ionization spectrometric imaging of brain sections showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 14 publications
(17 reference statements)
1
15
0
Order By: Relevance
“…Matrix assisted laser desorption ionization mass spectrometry imaging (MALDI MSI) is a label‐free technique, which offers the advantage of determining the distribution of parent drug and metabolites simultaneously . We have recently shown that a combination of liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) with MALDI MSI provides better correlation than PET imaging technique . The aim of this study was to establish methods for the preclinical evaluation and localization of fluoroquinolones in the rat brain by using LC‐MS/MS and MALDI MSI as sensitive tools for its determination.…”
Section: Introductionsupporting
confidence: 84%
“…Matrix assisted laser desorption ionization mass spectrometry imaging (MALDI MSI) is a label‐free technique, which offers the advantage of determining the distribution of parent drug and metabolites simultaneously . We have recently shown that a combination of liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) with MALDI MSI provides better correlation than PET imaging technique . The aim of this study was to establish methods for the preclinical evaluation and localization of fluoroquinolones in the rat brain by using LC‐MS/MS and MALDI MSI as sensitive tools for its determination.…”
Section: Introductionsupporting
confidence: 84%
“…The application of MSI to investigate small‐molecule spatial distribution was first demonstrated in 2003 following imaging of two anti‐cancer drugs, SCH 226 374 and compound A, in rat brain . Since then, a wide range of small molecules have been mapped using MSI in various biological tissues . MSI of antiretroviral drugs in various biological tissues has been done; however, there are no MSI‐related studies showing the spatial distribution of elvitegravir in biological tissues, and few studies have demonstrated the use of MSI to map tenofovir in situ .…”
Section: Resultsmentioning
confidence: 99%
“…The matrix solution was prepared by dissolving CHCA in 50% acetonitrile, 0.1% trifluoroacetic acid to make up a final concentration of 7 mg/mL. For matrix and ISTD application, a previously described standardized ImagePrep (Bruker Daltonics, Bremen, Germany) five‐cycle method was used, each cycle consisting of three steps including spraying, incubation and drying . An automated ImagePrep spraying equipment uniformly deposited the matrix onto the tissue in a form of an aerosol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We show that clofazimine exhibits minimal penetration of the blood-brain barrier, and its low solubility and high lipophilicity are also barriers to translation for brain tumors. There has been conflicting evidence for whether clofazimine is able to penetrate the brain; while some studies have reported no detectable levels in the brain (Baik et al, 2013;Holdiness, 1989), other studies detected a level of 156 ng/mL of clofazimine in the brain of mice treated with 25 mg/kg of the drug (Baijnath et al, 2015) and an effect on Kv1.3 channels in the brain in animals treated with 50 mg/kg clofazimine after traumatic brain injury (Reeves et al, 2016). In contrast, using the equivalent of the maximum tolerated human dose (2.44 mg/kg in mice), we were unable to detect clofazimine in the brain using mass spectrometry or the ability for it to cross the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%